Establishment and Partial Characterization of Three Novel Permanent Cell Lines Originating from European Freshwater Fish Species - Andor Doszpoly (Pathogens, 2025)
The establishment and partial characterization of three continuous cell lines from European freshwater fish species are provided. The three new cell lines, designated NPL-3, AF-1, and PF-1, were created from larvae of northern pike (Esox lucius) and fin tissues of asp (Leuciscus aspius) and European perch (Perca fluviatilis) fin tissues, respectively. All three cell lines have been subcultured more than 90 times since their establishment. Cells were optimally maintained at 25 °C in M199 medium supplemented with 10% fetal bovine serum. The NPL-3 and AF-1 cells are susceptible to spring viraemia of carp virus, pike fry rhabdovirus, ictalurid herpesvirus 2, and European catfish virus, while in the PF-1 cells, only the latter two viruses were successfully propagated. These newly established cell lines could serve as diagnostic tools for the aforementioned economically important viral diseases. They might be effective appliances for isolating novel viruses from northern pike, asp, European perch, and other closely related fish species.